(untitled) (Nativa, 2020)
As estimativas do volume de espécies nativas com uso de equações, sobretudo na região Amazônica, ainda apresentam incertezas sobre a qualidade estatística e sua comparação com o fator de forma. Assim, o presente estudo objetivou comparar as estimativas volumétricas obtidas com o emprego de equações de volume, fator de forma para estimativa de volume em área de concessão florestal na Floresta Nacional (Flona) do Jamari, Rondônia. Foram derrubadas 40 árvores com DAP≥50,0 cm de seis espécies diferentes para ajuste de modelos de volume de simples e dupla entrada e fator de forma médio, os quais foram comparados com outros métodos de estimativas de volume (modelos ajustados por meio de dados obtidos do romaneio na mesma área e fator de forma 0,7, conforme determinado pela legislação) pelo teste de Dunnett ao nível de 5% de probabilidade, utilizando-se como parâmetro para validação, o volume comercial rigoroso obtido da cubagem de outras 15 árvores com DAP≥50,0 cm. O modelo de Schumacher-Hall não linear foi o que apresentou melhor ajuste e o fator de forma médio foi de 0,7257, considerando todas as espécies. Verificou-se que as estimativas geradas pelos métodos não apresentaram diferenças estatísticas e de forma geral, esses subestimaram o volume comercial. Palavras-chave: florestas públicas; modelos volumétricos; fator de forma. EFFICIENCY OF METHODS FOR VOLUMETRIC ESTIMATION OF NATIVE SPECIES IN WESTERN AMAZON ABSTRACT: The methods of estimating the volume of native species are widely varied, with the use of widespread mathematical models as well as the application of the form factor. In general, to obtain volume in management plans in the Amazon, current legislation provides for the determination of productive stocks based on volume equations, except for the first year. However, there are still uncertainties about the statistical quality of these methods and which one is more accurate. Thus, the present study aimed to compare the volumetric estimates obtained with the use of volume equations, a form factor for volume estimation in a concession area in the Jamari National Forest (Flona), Rondônia. 40 trees were sampled with DBH≥50.0 cm for adjustment of single and double-volume volume models diffused in the scientific medium and average form factor, which were compared with other methods of volume estimation (models adjusted by means of data obtained from the romaneio in the same area and form factor 0.7), by Dunnett’s test, using as a parameter of comparison, the strict commercial volume obtained from the cubing of another 15 trees with DBH≥50.0 cm. The non-linear Schumacher-Hall model presented the best fit and the mean shape factor was 0.7257. It was verified that the estimates generated by the methods did not present statistical differences and, in general, the methods underestimated the commercial volume. Keywords: public forests; volumetric models; form fator.